Double-layer AGC frequency regulation control method considering operating economic cost and energy storage SOC consistency. (February 2023) - Guo, Menglei; Zheng, Jianyong; Mei, Fei; Sha, Haoyuan; Gao, Ang; Xie, Yang
Highlights: A novel dynamic wear coefficient based on power change rate. Optimizing the frequency regulation operation cost. A dynamic control of energy storage SOC that effectively suppress SOC fluctuation. Real-time adjustment of the SOC difference between energy storage units. Abstract: Aiming at the problem of power grid frequency regulation caused by the large-scale grid connection of new energy, this paper proposes a double-layer automatic generation control (AGC) frequency regulation control method that considers the operating economic cost and the consistency of the state of charge (SOC) of the energy storage. At the regional control level, an economically optimized dynamic frequency regulation responsibility distribution between the unit and the energy storage is realized, and the idle time of energy storage is fully used for SOC management to effectively suppress the fluctuation of the energy storage SOC. At the energy storage station level, the cooperative control algorithm is used to ensure that the output and SOC of each energy storage unit are consistent, respectively. The effectiveness of the method is verified by establishing the dynamic model of the unit-storage combined frequency regulation of the regional power grid for simulation and comparison experiments. The method proposed in this paper considers the influence of different disturbance conditions on the AGC frequency regulation responsibility distribution between the unit and the energy storage and fully uses the frequency regulation characteristics of the energy storage's rapid and flexible response. It effectively improves the service life of energy storage and the comprehensive operation efficiency of the system while optimizing the frequency regulation operation cost, improving the frequency regulation performance, and increasing the frequency regulation compensation income.